STRENGTHENING IMMIGRATION FUNCTION AS FACILITATOR OF COMMUNITY WELFARE DEVELOPMENT IN MOROTAI SPECIAL ECONOMIC ZONE - Filianto Akbar (Jurnal Ilmiah Kajian Keimigrasian, 2021)
Morotai Island Regency has a geoeconomic and geostrategic strategic location and is an area with great potential both in terms of tourism, the fishing industry, and various other industries. This potential has made the government set Morotai as a Special Economic Zone (SEZ) since 2014. This paper aims to find out the extent of the development of the Morotai SEZ on the regional economy and increase the welfare of the community, as well as know the role of immigration that can be carried out as a manifestation of one of the immigration functions, namelydevelopment public welfare. The results show that after the Morotai SEZ, although there has been an increase in local revenue, it has not significantly and consistently affected the economy due to the suboptimal use of local government over the potential of the Morotai SEZ. The role of the immigration function in the Morotai SEZ region must also be strengthened through the establishment of an immigration work unit in the Morotai SEZ region and the improvement of other immigration cooperation in order to facilitate the opening of international access, community mobility and business actors in various industries in Morotai, including other regions in eastern Indonesia, with the aim to improvethe welfare of the community.